2001
DOI: 10.2307/2657116
|View full text |Cite
|
Sign up to set email alerts
|

The dalbergioid legumes (Fabaceae): delimitation of a pantropical monophyletic clade

Abstract: A monophyletic pantropical group of papilionoid legumes, here referred to as the "dalbergioid" legumes, is circumscribed to include all genera previously referred to the tribes Aeschynomeneae and Adesmieae, the subtribe Bryinae of the Desmodieae, and tribe Dalbergieae except Andira, Hymenolobium, Vatairea, and Vataireopsis. This previously undetected group was discovered with phylogenetic analysis of DNA sequences from the chloroplast trnK (including matK) and trnL introns, and the nuclear ribosomal 5.8S and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
149
0
17

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(178 citation statements)
references
References 73 publications
12
149
0
17
Order By: Relevance
“…However, none of the previous studies clearly resolved the position of the Brongniartieae with respect to the other lineages of the Genistoids s.l. (Pennington et al, 2001;Wojciechowski et al, 2004;Cardoso et al, 2012aCardoso et al, , 2013a. Our ML and Bayesian analyses of the broad matK dataset of papilionoid legumes included a denser sampling in the Brongniartieae (63 accessions in 37 species of 13 genera sampled here vs. 18 accessions in 16 species of 10 genera in Cardoso et al, 2013a).…”
Section: The Brongniartieae Within the Genistoids Slmentioning
confidence: 97%
See 3 more Smart Citations
“…However, none of the previous studies clearly resolved the position of the Brongniartieae with respect to the other lineages of the Genistoids s.l. (Pennington et al, 2001;Wojciechowski et al, 2004;Cardoso et al, 2012aCardoso et al, , 2013a. Our ML and Bayesian analyses of the broad matK dataset of papilionoid legumes included a denser sampling in the Brongniartieae (63 accessions in 37 species of 13 genera sampled here vs. 18 accessions in 16 species of 10 genera in Cardoso et al, 2013a).…”
Section: The Brongniartieae Within the Genistoids Slmentioning
confidence: 97%
“…To accomplish this aim, all major lineages of the papilionoids (Cardoso et al, 2012a(Cardoso et al, , 2013a were included, mostly from previously published matK sequences (e.g., Hu et al, 2000;Lavin et al, 2001Lavin et al, , 2003McMahon and Hufford, 2004;Wojciechowski et al, 2004;Queiroz et al, 2010Queiroz et al, , 2015Queiroz and Lavin, 2011;Delgado-Salinas et al, 2011;Cardoso et al 2012aCardoso et al , 2013aCardoso et al , 2015Snak et al, 2016).…”
Section: Taxon Sampling and Molecular Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, all close relatives of both Pictetia and Poitea have been sampled exhaustively. For Pictetia, this includes four other genera in the trans-Atlantic Ormocarpum clade (Diphysa, Zygocarpum, Ormocarpopsis, and Ormocarpum;Lavin et al 2000;Thulin and Lavin 2001) as well as appropriate outgroups identified by Lavin et al (2001). For Poitea, this includes 10 other genera in the primarily North American tribe Robinieae (Hebestigma, Lennea, Gliricidia, Hybosema, Robinia, Poissonia, Coursetia, Olneya, Peteria, Genistidium, and Sphinctospermum;Lavin and Sousa 1995) as well as appropriate outgroups identified in a large-scale legume phylogeny derived from matK sequences (M. F. Wojciechowski, unpublished data).…”
Section: Taxon Samplingmentioning
confidence: 99%